In situ measurements of impact‐induced pressure waves in sandstone targets. Issue 10 (13th October 2014) - Hoerth, Tobias; Schäfer, Frank; Nau, Siegfried; Kuder, Jürgen; Poelchau, Michael H.; Thoma, Klaus; Kenkmann, Thomas
Abstract In the present study we introduce an innovative method for the measurement of impact‐induced pressure waves within geological materials. Impact experiments on dry and water‐saturated sandstone targets were conducted at a velocity of 4600 m/s using 12 mm steel projectiles to investigate amplitudes, decay behavior, and speed of the waves propagating through the target material. For this purpose a special kind of piezoresistive sensor capable of recording transient stress pulses within solid brittle materials was developed and calibrated using a Split‐Hopkinson pressure bar. Experimental impact parameters (projectile size and speed) were kept constant and yielded reproducible signal curves in terms of rise time and peak amplitudes. Pressure amplitudes decreased by 3 orders of magnitude within the first 250 mm (i.e., 42 projectile radii). The attenuation for water‐saturated sandstone is higher compared to dry sandstone which is attributed to dissipation effects caused by relative motion between bulk material and interstitial water. The proportion of the impact energy radiated as seismic energy (seismic efficiency) is in the order of 10−3. The present study shows the feasibility of real‐time measurements of waves caused by hypervelocity impacts on geological materials. Experiments of this kind lead to a better understanding of the processes in the crater subsurface during a hypervelocity impact.